Principles of project management under the influence of changes in environments of project implementation - A. A. Tikhomirov (Вестник университета)
This article discusses an approach to forming principles of project management under the influence of changes in the environments of project implementation. The consideration of the environment of changes affecting the implementation of the project is presented, namely the internal environment of the project implementation, the internal and external environment of the parent (permanent) organisation. Examples of organisations’ adaptation to transformations in business environments are given. In terms of emerging changes in environments of the project implementation, the authors characterised a trace of a single change from a formalised set of changes in a particular environment to a field of knowledge according to the methodology of the classical theory of project management. Based on the principles and methodology of the theory of systems, a generalised scheme for managing tasks arising during project implementation is formalised, a mathematical record of the elements of this scheme is given with consideration to their mutual influence. Special attention is paid to such a concept as a control error. The realisation of one of the tasks of project management is illustrated with another example, indicating compliance with the theory of system management. Examples of transformation and diversification processes of the parent (permanent) project organisation are examined. In conclusion, the author formulated 5 principles of project management in the context of changing implementation environments.